IDENTIFIKASI POTENSI DAYA TARIK WISATA PURA TANJUNG BUKUR DI LOMBOK UTARA - Karni, Ni Kadek; Artana, I Made Puja; Artini, Ni Nyoman Puji; Suardana, I Ketut Putu (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2023)
This article is a comprehensive analysis of Pura Tanjung Bukur, a spiritual tourist destination located on the island of Lombok, Indonesia. The research aims to understand the appeal of Pura Tanjung Bukur from the perspectives of spirituality, culture, and visitor experiences. Using a qualitative methodology, we conducted interviews with administrators, visitors, and local community leaders, and performed on-site observations. The analysis results indicate that Pura Tanjung Bukur possesses a strong attraction as a spiritual destination due to its rich history, supporting attractions, and religious practices. Furthermore, ongoing communication and active involvement of the local community in the management of Pura Tanjung Bukur have played a crucial role in sustaining this destination. This article offers profound insights into how Pura Tanjung Bukur has become a primary choice for those seeking spiritual experiences in Lombok and underscores the importance of sustainable communication strategies in maintaining the allure of spiritual tourism. This research holds significant implications for tourism destination managers and other stakeholders striving to develop sustainable spiritual destinations in various tourist locations.